Genetic Variability In Physico-Chemical And Morphological Traits Among Sandy Pear (Pyrus Pyrifolia Nakai.) Genotypes In North-Western Himalaya (Applied Biological Research, 2018)
The study was aimed to assess the genetic diversity in sandy pear (Pyrus pyrifolia Nakai.) of North-Western Himalayan state of Jammu & Kashmir (India) and to explore and characterize the available  genotypes using morphological traits. The genetic variability of 30 sandy pear genotypes collected from the 3 districts of Kashmir were  evaluated for various qualitative and quantitative traits. The  genotypes showed a considerable genetic diversity and differed  significantly for traits like tree, leaf, flower, fruit and yield characters.  Fruit weight, fruit firmness, total soluble solids, acidity, juiciness, total  sugars, yield and yield efficiency ranged from 21.7-200.4 g, 5.3-9.79 kg cm-2, 9.2-17.0oB, 0.11-0.46%, 32.88-84.05%, 4.50-11.15%, 10.0-805.0 kg tree-1and 0.14-1.72 kg cm-2, respectively, with respective mean values of 68.7±0.78 g, 7.52±0.03 kg cm-2, 12.93±0.08oB, 0.23±0.01%, 64.65 ±0.1%, 7.64±0.06, 177.56±0.46 kg tree-1and 0.57±0.004 kg cm-2. The  coefficient of variation was highest for fruit diameter (15.58%), followed by fruit length (10.87%) and lowest for juice content (0.28%), followed by yield (0.45%). Fruit diameter showed a  significant positive correlation with fruit length and fruit weight butnegative correlation of fruit diameter was observed with TSS, acidity  and sugars. Yield of sandy pear genotypes had positive correlation with yield efficiency.
Keywords: Clusters; correlation; genetic variability; sandy pear; yield